2006
DOI: 10.1021/la052303i
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Polymer Structure and Morphology on Talc Wettability

Abstract: Advancing water contact angles were measured on freshly cleaved talc faces as well as on talc particles. The intrinsic hydrophobicity of talc was shown to be due to the dominance of the apolar components of the work of adhesion. Polyacrylamides and polysaccharides adsorb onto the surface of talc, displaying strikingly different morphologies. Adsorbed amount, apparent layer thickness, and polymer structure control talc wettability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 37 publications
3
42
1
Order By: Relevance
“…Contrast in the phase image is used to indicate patchy coverage of an adsorbate layer, with the underlying substrate expected to produce a different phase response to the oscillating cantilever than a soft adsorbate layer. Unlike in some of our other investigations of adsorbed polymers on hydrophobic surfaces [9,10,22,41], the phase image does not provide any clear contrast for any of the polymers, indicating that they all form complete layers on the model hydrophobic surface.…”
Section: Atomic Force Microscope (Afm) Imaging Of Adsorbed Dextrinscontrasting
confidence: 96%
See 1 more Smart Citation
“…Contrast in the phase image is used to indicate patchy coverage of an adsorbate layer, with the underlying substrate expected to produce a different phase response to the oscillating cantilever than a soft adsorbate layer. Unlike in some of our other investigations of adsorbed polymers on hydrophobic surfaces [9,10,22,41], the phase image does not provide any clear contrast for any of the polymers, indicating that they all form complete layers on the model hydrophobic surface.…”
Section: Atomic Force Microscope (Afm) Imaging Of Adsorbed Dextrinscontrasting
confidence: 96%
“…The polymers (regular wheat dextrin -Dextrin TY; phenyl succinate dextrin -PS Dextrin; and styrene oxide dextrin -SO Dextrin) have been selected to enable us to investigate subtle effects in adsorption and dewetting due to minor variation in the substitution chemistry of a commonly studied flotation depressant [5,20,21]. The model hydrophobic surface (mixed -CH 3 and -OH-terminated alkanethiol layer on gold) has been chosen to give a contact angle similar to many hydrophobic minerals [22]. The substrate also presents no functional groups likely to interact with the adsorbing polymers through any form of chemical or strong physical interaction (-CH 3 is inert; -OH will not deprotonate except at very high pH).…”
Section: Introductionmentioning
confidence: 99%
“…4 -is presumably caused by the extended conformation of polymer in solution at low electrolyte concentration. Similar network morphologies have been observed for non-ionic hydroxypropylated starch adsorbed on talc surface [40]. In that case, however, the network structures are speculated to form already during adsorption, not by dewetting.…”
Section: Starch Films Deposited On Hydrophobic Silicasupporting
confidence: 77%
“…It is more likely that the difference is due to some interaction between the carboxyl group of the CMC polymer and the surface of molybdenite. Such an interaction can be ruled out for CMC on talc as the morphology adopted for CMC on talc is not dissimilar to that observed for many dextrin polymers (substituted and unsubstituted) [19] and polyacrylamides [22] on talc. It is the morphology of CMC on molybdenite that is unusual for a polymer depressant on an 'inert' hydrophobic basal plane.…”
Section: Discussionmentioning
confidence: 98%
“…A rock molybdenite sample from the Northern Territory was provided by the Mineralogy Department of the South Australia Museum. A piece of sticking tape was used to peel the top layer of the talc and molybdenite samples, revealing flat freshly cleaved basal plane [22]. Our previous X-ray photoelectron spectroscopy (XPS) analysis has revealed that all flat mineral surfaces and particles were free from significant impurities [20].…”
Section: Methodsmentioning
confidence: 99%